1999
DOI: 10.1007/s004050050186
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin deficiency and determination of pneumococcal antibody titers in patients with therapy-refractory recurrent rhinosinusitis

Abstract: We examined 245 patients with chronic rhinosinusitis not responding to prolonged antibiotic treatment and tested each patient for humoral antibody deficiencies. Low immunoglobulin levels were found in 22 patients. Five of them had defects of two or more immunoglobulin isotypes that were diagnosed as common variable immunodeficiency (CVI). Seventeen had an IgG-subclass deficiency. Before and after immunization with pneumococcal vaccine, serotype-specific pneumococcal antibody levels were determined to further e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 15 publications
1
38
2
2
Order By: Relevance
“…A similar study done by Cunningham-Rundles and Bodian (17) showed that 243 out of 248 patients with CVID (98%) had recurrent sinusitis, otitis, or bronchitis, and according to another study in 1989 (18), 22% had developed chronic lung disease. Also, some studies show that resistant sinus infection can frequently be the first presenting symptom in immune deficiencies, especially antibody deficiencies (10,38,48), and the infections of the upper respiratory tract occur several years before the appearance of lower respiratory tract infections (34). Once the infections of the lower respiratory tract have started, the patients neglect the symptoms from the upper respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study done by Cunningham-Rundles and Bodian (17) showed that 243 out of 248 patients with CVID (98%) had recurrent sinusitis, otitis, or bronchitis, and according to another study in 1989 (18), 22% had developed chronic lung disease. Also, some studies show that resistant sinus infection can frequently be the first presenting symptom in immune deficiencies, especially antibody deficiencies (10,38,48), and the infections of the upper respiratory tract occur several years before the appearance of lower respiratory tract infections (34). Once the infections of the lower respiratory tract have started, the patients neglect the symptoms from the upper respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of CRS patients with IgG subclass deficien-cies also had abnormally low baseline pneumococcal titers, with several individuals failing to adequately respond to Pneumovax. 2,7,20,21 Although the aforementioned studies focused on IgG subclass deficiency and also described SAD in that context, there are very few studies that focus solely on the role of SAD in CRS. A recent retrospective study by Carr examined 129 patients with medically refractory CRS, requiring multiple surgeries.…”
Section: Sad and Crsmentioning
confidence: 99%
“…The challenging task confronting clinicians is that the severity or intervals of disease do not point to an underlying cause. 7 In the case of immunodeficiency, the severity of CRS symptoms may not directly relate to an underlying immune dysfunction; however, an immunodeficiency may make disease more refractory to standard therapies. 8 This points to the importance of identifying the etiology of disease in a patient with refractory CRS, because treatment decisions can be significantly influenced.…”
Section: Refractory Crsmentioning
confidence: 99%
See 1 more Smart Citation
“…May y su equipo, en Alemania, 1999, 16 encontraron niveles bajos de inmunoglobulinas en 22 de 245 pacientes con rinosinusitis crónica refractaria (17 deficiencia de subclases de IgG, 5 inmunodeficiencia común variable, 3 defecto Figura 6. IgE sérica total por edad en 16 pacientes pediátricos sometidos a cirugía de otorrinolaringología por infecciones respiratorias.…”
Section: Conclusionesunclassified